The transversus abdominis plane block may reduce early postoperative pain after laparoscopic ventral hernia repair: A matched pair analysis. (July 2020) - Paasch, C.; Aljedani, N.; Ortiz, P.; Azarhoush, S.; Fiebelkorn, J.; Boettge, K.A.; Gauger, U.; Anders, S.; De Santo, G.; Strik, M.W.
Abstract: Purpose: Patients suffering from a ventral hernia can be treated by laparoscopic ventral hernia repair (VHR) with the intraperitoneal onlay mesh (IPOM) technique. To reduce early postoperative pain and the analgesic cumulative need for medication (CNM), the transversus abdominis plane (TAP) block has recently been investigated and implemented in hernia surgery. We aimed to investigate its impact when conducting a VHR in IPOM technique. Methods: A single center retrospective observational matched pair analysis has been conducted from March to April 2020. The data of patients who underwent VHR in IPOM technique with prior TAP block administration were enrolled. The matching was performed using the variables age ( ±5 years), gender, type of surgery, BMI and ASA stage. Results: 52 patients were enrolled. Among the individuals of the TAP block group, (18 males, 8 females) the average age was 52.4 (15.9). The average BMI was 29.0 (3.95) kg/m 2 . 14 patients suffered from an umbilical, 9 from an incisional, and three from an epigastric hernia. Except for COX-2-inhibitors, (TAP group: 41.9 mg (31.0), Control group 9.23 (22.1), p < 0.001) the analgesic CNM of both groups did not statistically differ from each other. The literature review yielded four relevant publications (n = 100). The authors stated a positive impact of the TAP block on early postoperative pain and analgesic medication consumption. Conclusion: The TAP block prior to laparoscopic ventral hernia repair may reduce early postoperative pain and analgesic medication consumption in selected patients. More randomized clinical trials are needed to confirm these findings. Highlights: The transversus abdominis plane block may reduce early postoperative pain after laparoscopic ventral hernia repair. Four relevant publication (n = 100) has been yielded on that topic. Review findings are contradictorily.